BANKING INDICATORS IN DOING START-UP FUNDING FOR CREATIVE INDUSTRY IN INDONESIA - Annisa, Rinda Nur; Hatammimi, Jurry; Rizal, Nora Amelda (The journal of contemporary issues in business and government, 2021)
The development of creative industry start-ups has impacts on several aspects of the Indonesian economy. However, this industry has an obstacle, namely the difficulty of getting access to funding, including from the bank. The purpose of this study is to find out the indicators that are considered by banks from the loan/credit/funding variable. The indicators are business stage, investment period and financing model. The object of this research is banking which is part of the State-Owned Enterprises (SOE).This study is used qualitative data methods. The methods that is used in this study to get the data is semi-structured interview. This study is used triangulation of sources, to reduce the subjectivity. The result is that the loan/credit/funding variable influences the decision on access to funding. The implication of this research is to make ease the start-up especially for creative industry to get the funding from the bank.